2009
DOI: 10.1111/j.1525-139x.2009.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

PROGRESS IN UREMIC TOXIN RESEARCH: Guanidino Compounds as Uremic (Neuro)Toxins

Abstract: Neurological and vascular impairment are important sources of morbidity in patients with renal failure. A portion of patients still suffers from uremic encephalopathy or other signs of nervous system impairment. Several reports demonstrate increased incidence of cardiac infarction and cerebrovascular accidents in chronic renal failure patients, even in those otherwise adequately dialyzed. Epileptic and cognitive symptoms are among the most typical manifestations of uremic encephalopathy. Several guanidino comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 32 publications
(42 reference statements)
0
90
1
7
Order By: Relevance
“…79 DeDeyn et al reported that cerebrospinal fluid and brain levels of some guanidine compounds, such as creatinine, guanidine, guanidinosuccinic acid, and methylguanidine, are substantially elevated in uremic patients. 80 Interestingly, these high toxin concentrations (up to 10-fold higher in CKD patients than in controls) were found in brain regions that play a determinant role in cognition, such as the thalamus, the mammillary bodies, and the cerebral cortex. 80 It is well known that these uremic guanidine compounds are neuroexcitatory agents and have convulsant activity in animal studies.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…79 DeDeyn et al reported that cerebrospinal fluid and brain levels of some guanidine compounds, such as creatinine, guanidine, guanidinosuccinic acid, and methylguanidine, are substantially elevated in uremic patients. 80 Interestingly, these high toxin concentrations (up to 10-fold higher in CKD patients than in controls) were found in brain regions that play a determinant role in cognition, such as the thalamus, the mammillary bodies, and the cerebral cortex. 80 It is well known that these uremic guanidine compounds are neuroexcitatory agents and have convulsant activity in animal studies.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 99%
“…80 Interestingly, these high toxin concentrations (up to 10-fold higher in CKD patients than in controls) were found in brain regions that play a determinant role in cognition, such as the thalamus, the mammillary bodies, and the cerebral cortex. 80 It is well known that these uremic guanidine compounds are neuroexcitatory agents and have convulsant activity in animal studies. 81 However, it is still not clear whether uremic toxins are directly responsible for cognitive impairment.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 99%
“…Argininemia treatments that successfully lower arginine and guanidino compounds levels should prevent neurological symptoms, but although arginine plasmatic levels may normalize under conventional treatment, the arginine's catabolites can remain elevated (Marescau et al 1990), and some of these guanidino compounds are neurotoxic (De Deyn et al 2009;Hiramatzu, 2003). In both of our patients, arginine concentration decreased significantly under conventional treatment (but never normalized), and guanidine compounds were markedly elevated in plasma and urine.…”
Section: Discussionmentioning
confidence: 67%
“…Another possibility is that, together with urea, other uremic solutes antagonizing its toxic impact are retained (Lee et al, 1991). Finally, urea might be at the origin of other, more toxic moieties, such as some of the guanidines or carbamylation products (De Deyn et al, 2003;De Deyn et al, 2009;Stim et al, 1995;Vanholder & De Smet, 1999) .…”
Section: Uremic Toxinsmentioning
confidence: 99%
“…Based on the results summarized above, a hypothetical mechanism for the action of uremic guanidino compounds on glutamatergic transmission in the central nervous system was proposed by De Deyn et al (De Deyn et al, 2009) (Fig. 2).…”
Section: Hypothetical Mechanism Of Neuroexcitation By Uremic Guanidinmentioning
confidence: 99%